Pengaruh Kepemimpinan Kepala Sekolah Terhadap Kinerja Guru Pada Guru SMP PGRI Suryakencana Cilengsi - Saring Arianto; Idha Isnaningrum (Jurnal Ilmu Pendidikan dan Sosial, 2023)
This study aims to find out about the influence of the principal's leadership on teacher satisfaction at SMP PGRI Suryakencana Cileungsi. The research method used is a quantitative method with a survey approach. Primary data source; Principals, teachers and secondary data sources; relevant books, journals and websites. The research instrument was a questionnaire to be filled out by 34 teachers as the research sample, as well as the research population. The research instrument was first tried out to determine the validity and reliability of the items. The data analysis used is simple regression. Before calculating the correlation coefficient, a requirements analysis test was held, namely the data normality test and linearity test. Linear analysis test results, sign value. 0.000 <0.05 then Ho is rejected. The results of the significant level test value F count = 84.400 > F table (df: 1.32) = 4.15, then Ho is rejected, meaning the correlation coefficient is significant. So one conclusion was obtained that "There is a significant influence of the leadership of the principal on teacher performance at SMP PGRI Suryakencana Cileungsi".